Fetal Limb Ischaemia in Twin-to-Twin Transfusion Syndrome - Mark Kilby; Rachel Pounds; Paul Mannix (Case Reports in Pediatrics)
Objective. To describe the rare association between prenatal vascular limb occlusion and twin-to-twin transfusion syndrome. The Case. A woman with severe twin-to-twin transfusion syndrome was treated with fetoscopic laser ablation at 19-week gestation. At 27 weeks, the twins were delivered by an emergency caesarean section. The right arm of twin 1, the recipient twin, was noted to be “ischaemic” and was later amputated. Conclusion. This case is unusual in that it affected the upper limb and there was no evidence of polycythaemia, which is a suggested pathological mechanism. It was initially thought that the limb damage was due to the laser ablation, but after discussion with the fetal medicine team vascular limb occlusion in association with twin-to-twin transfusion syndrome was considered. Limb ischaemia is a serious complication of twin-to-twin transfusion syndrome and is unrelated to any form of fetal therapy. Implications. Neonatologists and paediatricians need to be aware of this association as it has medicolegal implications and parents should be counselled as to the possible, albeit rare, occurrence, especially when twin-to-twin transfusion syndrome is of advanced stage at presentation.